Face and gaze perception in borderline personality disorder: An electrical neuroimaging study. (30th November 2017) - Berchio, Cristina; Piguet, Camille; Gentsch, Kornelia; Küng, Anne-Lise; Rihs, Tonia A.; Hasler, Roland; Aubry, Jean-Michel; Dayer, Alexandre; Michel, Christoph M.; Perroud, Nader
Abstract: Humans are sensitive to gaze direction from early life, and gaze has social and affective values. Borderline personality disorder (BPD) is a clinical condition characterized by emotional dysregulation and enhanced sensitivity to affective and social cues. In this study we wanted to investigate the temporal-spatial dynamics of spontaneous gaze processing in BPD. We used a 2-back-working-memory task, in which neutral faces with direct and averted gaze were presented. Gaze was used as an emotional modulator of event-related-potentials to faces. High density EEG data were acquired in 19 females with BPD and 19 healthy women, and analyzed with a spatio-temporal microstates analysis approach. Independently of gaze direction, BPD patients showed altered N170 and P200 topographies for neutral faces. Source localization revealed that the anterior cingulate and other prefrontal regions were abnormally activated during the N170 component related to face encoding, while middle temporal deactivations were observed during the P200 component. Post-task affective ratings showed that BPD patients had difficulty to disambiguate neutral gaze. This study provides first evidence for an early neural bias toward neutral faces in BPD independent of gaze direction and also suggests the importance of considering basic aspects of social cognition in identifying biological risk factors of BPD. Highlights: This study provides evidence for an early neural bias toward neutral faces in BPD. BPD patients showed altered N170 and P200 topographies for neutral faces. The anterior cingulate was abnormally activated during the N170 component. BPD patients had difficulty to disambiguate neutral gaze.